(untitled) (Revista Brasileira de Ciências Farmacêuticas, 2007)
Reactive oxygen species (ROS) and free radical species have been implicated in initiating, accompanying or causing many diseases in living organisms; there is thus, a continual need for antioxidants molecules to inactivate ROS/free radicals. Many studies of plants crude extracts have demonstrated free-radical scavenging and antioxidant action. Maytenus species have long been used, in several countries, as traditional medicines against gastric ulcers, dyspepsia and others gastric problems and for their anti-inflammatory properties. In this study, Maytenus aquifolium (Celastraceae) root bark ethanol extract was assessed for its ability to scavenge free radicals and reactive oxygen species. The results were expressed as percentage inhibition of the active species. The extract was efficient against studied reactive species: DPPH radical (obtained inhibition = 35.5 ± 1.3 %), ABTS+ (IC50 = 0.0036 ± 0.0003 mg/mL), HOCl (IC50 = 0.002 ± 0.0001 mg/mL ), O2- (obtained inhibition = 36.0 ± 2.1 %), and NO (obtained inhibition = 18.3 ± 0.4 %).